Design, synthesis and biochemical evaluation of novel carbonic anhydrase inhibitors triggered by structural knowledge on hCA VII. (15th August 2021) - Mancuso, Francesca; Di Fiore, Anna; De Luca, Laura; Angeli, Andrea; De Simone, Giuseppina; Supuran, Claudiu T.; Gitto, Rosaria
Graphical abstract: Highlights: The crystal complex with hCA VII highlighted the main interaction within the enzymatic catalytic site. A series of of 4-(4(hetero)aroylpiperazine-1-carbonyl)benzene-1-sulfonamides were synthesized. All compounds inhibited druggable human CA isoforms. Several derivatives were active at nanomolar concentration against hCA VII. Abstract: To tackle the challenge of isoform selectivity, we explored the entrance of the cavity for selected druggable human Carbonic Anhydrases (hCAs). Based on X-ray crystallographic studies on the 4-(4-(2-chlorobenzoyl)piperazine-1-carbonyl)benzenesulfonamide in complex with the brain expressed hCA VII (PDB code: 7NC4), a series of 4-(4(hetero)aroylpiperazine-1-carbonyl)benzene-1-sulfonamides has been developed. To evaluate their capability to fit the hCA VII catalytic cavity, the newer benzenesulfonamides were preliminary investigated by means of docking simulations. Then, this series of thirteen benzenesulfonamides was synthesized and tested against selected druggable hCAs. Among them, the 4-(4-(furan-2-carbonyl)piperazine-1-carbonyl)benzenesulfonamide showed remarkable affinity towards hCA VII ( K i : 4.3 nM) and good selectivity over the physiologically widespread hCA I when compared to Topiramate (TPM).